Mode of formation of synovial villi. Issue 5 (October 1983) - Edwards, J C; Mackay, A R; Sedgwick, A D; Willoughby, D A
Abstract : Synovial tissue from 6 normal pigs and from 16 patients undergoing arthrotomy for joint disease was examined by dissecting microscopy. Scale models were constructed of 3 human synovial specimens from photographic magnifications of serial sections. Surface bridging and subintimal cavitation were observed, particularly in tissue from patients with rheumatoid arthritis. These features suggest that synovial surface projections (villi) do not form simply by outgrowth. Reference to original haematoxylin and eosin stained sections suggested that tissue splitting contributes to the formation of villi.